Molecular mechanisms involved in the interaction of Neisseria meningitidis with cells of the human blood–cerebrospinal fluid barrier. Issue 2 (3rd March 2017) - Schubert-Unkmeir, Alexandra
Abstract: Neisseria meningitidis is one of the most common aetiological agents of bacterial meningitis, affecting predominantly children and young adults. The interaction of N. meningitidis with human endothelial cells lining blood vessels of the blood–cerebrospinal fluid barrier (B-CSFB) is critical for meningitis development. In recent decades, there has been a significant increase in understanding of the molecular mechanisms involved in the interaction of N. meningitidis with brain vascular cells. In this review, we will describe how N. meningitidis adheres to the brain vasculature, may enter inside these cells, hijack receptor signalling pathways and alter host-cell responses in order to traverse the B-CSFB. Abstract : This review provides an overview of research how Neisseria meningitidis adheres to the brain vasculature, may enter inside these cells, hijack receptor signalling pathways and alter host-cell responses in order to traverse the B-CSFB.